Argentina`s Housing Market in the 2000s - Marcela Cristini; Ramiro Moya; Guillermo Bermudez (Inter-American Development Bank (IDB), 2011)
In the last three decades, the supply of housing in Argentina has not kept pace with demand. This study analyzes the main drivers of Argentinas housing market and relates them to the macroeconomic environment in order to advance a policy agenda for housing policy reform. The demand for housing was calculated and tenure choice was analyzed. Structural characteristics affecting Argentinas housing market include the high concentration of the urban population in a few large metropolitan areas, the association of urban poverty with the housing deficit, and overcrowding. The mortgage market lost its appeal following the 2001-02 crisis due to widespread breaches of contract legitimized through protective legislation (still in place), insufficient long-term financing, and high inflation. The housing deficit could be eliminated in five to eight years if well-coordinated policy initiatives to develop the mortgage market and provide low-income housing were adopted under a decentralized, demand-driven, subsidized program.
Keywords: O54; R21; R23; R28; R30; R31; R38; R58; 330